Assessment of the Risk of Fractures Because of Service on Diesel Submarines: A Retrospective Cohort Study. Issue 7 (1st July 2015) - Saad, Amit; Kala, Carmel; Ohayon, Sharon; Feldman, Lior; Galili, Eran; Yanir, Yoav; Nemet, Dan; Netzer, Itamar
ABSTRACT: Introduction: Submariners are known to have decreased bone mass following periods of long submersion. We examined whether this produces a higher predilection to fractures. Methods: This is a retrospective cohort study. Data were collected from the computerized medical records of 457 consecutive submariners (serving 1091.42 man-years). The control group included 3, 219 consecutive sailors, (serving 5845.04 man-years). Groups were stratified according to age at induction, body mass index, place of birth, and status of service (i.e., compulsory versus professional). Analysis of fracture incidence and comparison of proportions between the groups was conducted using χ 2 tests and Fisher's exact test. The hazard ratio for fractures was performed using a survival analysis regression model for each group (Cox Proportional Hazard Model). Results: Nineteen submariners (4.2%) and 94 sailors (2.9%) were shown to have fractures during their service (RR = 1.42, p = 0.15). A Cox proportional hazard model was employed. No statistically significant difference was found between the 2 groups (HR = 1.037, p = 0.89). No correlation was found between length of service and risk of fracture. Most fractures suffered by submariners occurred outside their work environment. Conclusions: Submariners are repeatedly exposed to prolonged submersions that are deleterious to bone strength. However, no statistically significant difference in the incidence of fractures was found between submariners and surface sailors. This is an important finding for the bone and occupational health of submariners in general.